Application of Double Exponential Smoothing Method for Forecasting Laptop Sales - Nurhayati, Rafika; Yusron, Rizqi Darma Rusdiyan; Sabilla, Wilda Imama; Rosiani, Ulla Delfana (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
PT Indo Bismar is a retail company focused on laptop sales. The company experiences fluctuations in laptop sales each month, which impacts inventory management as it becomes challenging to predict demand accurately. Consequently, PT Indo Bismar faces financial losses due to unsold laptops. To address this issue, a sales forecasting system has been designed to optimize inventory management more effectively and efficiently.This study applies the double exponential smoothing method to forecast laptop sales and uses the Mean Absolute Percentage Error (MAPE) to measure forecasting accuracy. The double exponential smoothing method was tested through a trial-and-error approach. This process produced varying alpha and beta values for different laptop brands and models. It involved repeated iterations to test each combination until the optimal values that yielded the best forecasting accuracy were identified. After obtaining the MAPE results through the trial-and-error approach, the average system MAPE was calculated to evaluate the overall accuracy of the system, resulting in 16.58%. This indicates that the sales forecasting system demonstrates good accuracy, as the error rate falls within the range of 10% to 20%. Therefore, the use of the double exponential smoothing method can assist PT Indo Bismar in managing inventory and making strategic decisions for future laptop sales